(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article, breeding of broiler chicks is carried out in large groups of the same age in houses equipped with non-replaceable thick bedding and battery cages. Effective use of production rooms is ensured when growing broiler chicks in cages.